IMPLICATIONS OF PERMEABILITY AND ITS ANISOTROPY IN A MICA GOUGE FOR PORE PRESSURES IN FAULT ZONES - Zhang S.; Tullis T.E.; Scruggs V.J. (My University, 2001)
Large permeability anisotropy due to anisotropic alignment of clay shape fabric may play an important role in focusing fluid flow along fault zones in clay rich rocks. The degree of permeability anisotropy depends on the differences in tortuosity of the fluid flow path and mean pore aperture, which are of a function of effective stress. We have conducted hydrostatic compaction and frictional sliding experiments on 1mm thick artificial muscovite gouge layers with grain size <90μm, at normal stresses on the layer ranging from 25 to 125MPa. Permeability was measured both perpendicular and parallel to the gouge layer using water as pore fluid. Shear displacement up to 200mm was achieved. During initial packing and subsequent hydrostatic compaction, muscovite basal planes were aligned parallel to the fault plane, leading to the largest possible contrast in tortuosity between flow path perpendicular and parallel to the fault zone. We found that fluid permeability parallel to the fault zone is about one order of magnitude higher than perpendicular to it and that the magnitude of permeability anisotropy does not change with increasing normal stress. During shear deformation, the permeability anisotropy decreased with increasing shear displacement, an effect interpreted as being due to progressive rotation of muscovite basal planes away from the fault plane. Previous hydrogeological modelling has shown that permeability anisotropy on the order of 3-5 orders of magnitude is needed to effectively focus fluid flow along fault zones. Thus, our results seem to indicate that fabric anisotropy alone is not enough to cause focused fluid flow along natural fault zones. During hydrostatic compaction of muscovite gouge, a linear relationship holds between ln permeability and normal stress and the slope is about 0.03MPa-1, which is higher than for most porous sandstones. The value is reduced to about 0.006MPa-1 after shear deformation. The values are lower by 1-2 orders of magnitude than the value used in Rice's fault model, suggesting that maintaining high pore pressures would be harder than he assumed.
Keywords: FAULT SLIP; PERMEABILITY; ANISOTROPY